Scale-up of the jetcutter technology - Pruesse Ulf; Jahnz Ulrich; Wittlich Peter; Vorlop Klaus-Dieter (Hemijska Industrija, 2003)
The JetCutter is a new, simple and efficient technology for the high throughput encapsulation of various materials inside spherical beads. Monodisperse beads in the particle size range from approximately 0.2 mm up to several millimeters can be prepared at high throughput rates with the JetCutter. The generation of beads is not limited by the fluid viscosity. Thus, also highly viscous fluids even with high loadings of solids, can be processed, which leads to an improved stability of the resulting beads. The JetCutter technology is available in different scales and corresponding throughputs ranging from lab-scale devices (liters per day) up to large scale installations for industrial production purposes (tons per day). The application of the JetCutter for industrial purposes has been well established by geniaLab®, which currently produces more than 40 tons/year of small hydrogel beads.